Impulsive buying behavior as the main driver of college students' intention to use buy now, pay later (BNPL) services - Dewi Khornida Marheni; Felix Fajar Natanael Panjaitan; Yulfiswandi Yulfiswandi (Universitas Nusa Cendana, 2026)
This study examines the influence of financial parenting and impulse buying behavior on the intention to use Buy Now, Pay Later (BNPL) services among university students, with financial self-efficacy serving as a mediating variable. As BNPL services continue to gain popularity among younger consumers, understanding the behavioural and financial factors that drive adoption has become increasingly important for promoting responsible financial decision-making. Employing a quantitative research approach, data were collected from student respondents and analyzed to assess the direct and indirect relationships among the variables. The findings reveal that financial parenting does not significantly influence either financial self-efficacy or the intention to use BNPL services. Similarly, financial self-efficacy was found to have no significant effect on BNPL usage intention and did not mediate the relationship between financial parenting and BNPL adoption. In contrast, impulse buying behavior exerts a positive and significant influence on the intention to use BNPL, indicating that spontaneous purchasing tendencies are a primary driver of deferred-payment service adoption among students. These findings suggest that psychological and behavioural factors may play a more influential role than financial socialization or self-confidence in financial management when shaping BNPL usage intentions. The study contributes to the growing literature on consumer finance, financial technology adoption, and youth financial behaviour by highlighting the importance of addressing impulsive consumption tendencies through targeted financial education and responsible spending initiatives to reduce future financial vulnerability. Keywords: Buy Now Pay Later (BNPL); Financial Parenting; Financial Self-Efficacy;Impulsive Buying; Intention to Use BNPL